Fig-tree and sun: a dangerous association. - Di Terlizzi, L.; Pisani, V. (European Journal of Pediatric Dermatology, 2018)
The fig-tree belongs to the family of Moraceae. It is diffuse in the Mediterranean area. According to a popular belief the latex produced by the just picked figs and by the leaves has therapeutical properties. The farmers use the fig latex to treat stings, with better results - in their opinion - than the steroid creams. In the country of the South of Italy the fig latex is the most popular treatment of warts. It has also been considered able to eliminate freckles and lentigo. Finally, teen-agers use the decoction obtained from fig leaves to obtain a rapid and intense tanning. However, the results do not always come up to their expectation.